IMAGE COMPARISON OF SPIN ECHO, TURBO SPIN ECHO AND FLUID ATTENUATED INVERSION RECOVERY TO MRI USING HISTOGRAM IMAGES - RIBKA SETIAWATI (NIM:10207010); Pembimbing : Dr. rer.nat. Freddy Haryanto
Magnetic Resonance Imaging (MRI) is an imaging technique which utilizes magnetic moment property of the nucleus inside of body. Resonance will make the protons emit an electromagnetic wave which then will be processed to make an image. Pulse Sequence determines what kind of image that will be obtained. Sequences can be chosen using the right parameters. In MRI, some of the sequences are Spin Echo, Turbo Spin Echo and Fluid-Attenuated Inversion Recovery (FLAIR). In this study, images from those three sequences were obtained and processed. The images were obtained using an 1,5 Tesla MRI device at Santosa Bandung Interational Hospital using the library parameters. The image histograms were extracted from each image and were treated using statistik data analysis. The result of the calculation will show the characteristic of every sequence. Anatomical images are obtained from Spin Echo with T1-weighting, pathological images are obtained from Turbo Spin Echo with T2-weighting, and FLAIR can detects stroke disease.